Pengaruh Pembiayaan Murabahah, Musyarakah, dan Ijarah Terhadap Pertumbuhan Aset Bank Umum Syariah Yang Terdaftar Di OJK Periode 2018-2023 - Nisrina Athira Nasution; Cupian (Journal of Islamic Economics and Finance, 2024)
This study analyzes the impact of murabahah, musyarakah, and ijarah financing on the asset growth of Islamic commercial banks in Indonesia from 2018-2023 using the FGLS method for panel data analysis. Results indicate that murabahah and musyarakah financing positively affect asset growth, while ijarah financing negatively affects it. These findings offer valuable insights for Islamic banks, regulators, and policymakers in Indonesia.